Edge Computing in E-commerce Business: Economic Impacts and Advantages of Scalable Information Systems - Silitonga, Dikson; Rohmayanti, Siti Alfia Ayu; Aripin, Zaenal; Kuswandi, Dadi; Sulistyo, Arif Budi; Juhari (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Edge Computing brings better responsiveness and faster customer experiences, while Scalable Information Systems enable efficient business growth management. OBJECTIVE: This research analyzes the economic impact of using Edge Computing in E-Commerce businesses and reveals the advantages of Scalable Information Systems. METHOD: The research approach used is a mixed-method, which includes quantitative data analysis and interviews with key stakeholders in five E-Commerce companies. RESULTS: The research results show increased responsiveness, operational efficiency, cost savings, enhanced data security, and better customer retention due to the implementation of Edge Computing. Scalable Information Systems also help E-Commerce companies manage rapid business growth flexibly. CONCLUSION: This technology provides significant and relevant advantages in improving company performance and competitiveness in a competitive E-Commerce context.